Competitive advantage of intercultural communication knowledge among homestay entrepreneurs in Malaysian context - Zaleha Mohamad, Isma Rosila Ismail, Roswati Abd Rashid, (Opción, 2019)
This concept paper will discuss the competitive advantage of intercultural communication knowledge among the homestay entrepreneur in Malaysian context such as the cultural values, religion, customs and etiquette via comparative qualitative research methods. As a result, cultural values, religion, customs and etiquette at the target countries is one of the effective strategies in launching communication between the tourists and the hosts. In conclusion, effective communication will ultimately contribute to the smooth running of a tour which indirectly affects the quality of a vacation experience.